KHẢO SÁT ẢNH HƯỞNG CỦA HÀM LƯỢNG PHOTPHO ĐẾN TÍNH CHẤT LỚP PHỦ Ni-P VÀ ĐÁNH GIÁ KHẢ NĂNG CHỐNG ĂN MÒN CỦA LỚP PHỦ Ni-P ĐA LỚP ĐEN - Nguyễn, Thị Yến (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
INVESTIGATE THE EFFECTS OF PHOSPHORUS CONTENT ON PROPERTIES OF Ni-P COATING AND EVALUATE THE CORROSION RESISTANCE OF BLACK MULTILAYER Ni-P COATINGThe paper presents the effects of NaH2PO2 concentrations in electrodeposition solution on phosphorus contents and corrosion resistance of Ni-P layer. The results of SEM/EDX show that when the concentration of NaH2PO2 in solution increases, the content of phosphorus and corrosion resistance of the layer also increase and the alloy's state changes from coarse granules to a smooth surface. The paper also describes the electrodeposition method to make black Ni-P multilayer coating. The corrosion resistance of black multilayer Ni-P alloys including Ni-P (high phosphorus)/Ni-P (low phosphorus)/black Ni-P-Zn is 6 times higher than that of blackened steel when testing using salt spray methods.